Internally Randomized Control Trial of Radiation Exposure Using Ultra-low Radiation Imaging Versus Traditional C-arm Fluoroscopy for Patients Undergoing Single-level Minimally Invasive Transforaminal Lumbar Interbody Fusion. Issue 4 (15th February 2017) - Wang, Timothy Y.; Farber, S. Harrison; Perkins, Scott S.; Back, Adam G.; Byrd, Sarah A.; Chi, Debbie; Vincent, David; Karikari, Isaac O.
Abstract : Study Design: Randomized controlled trial. Objective: To compare radiation exposure between ultra-low radiation imaging (ULRI) with image enhancement and standard-dose fluoroscopy for patients undergoing minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Summary of Background Data: Although the benefits of MIS are lauded by many, there is a significant amount of radiation exposure to surgeon and operating room personnel. Our goal with this work was to see if by using ultra-low dose radiation settings coupled with image enhancement, this exposure could be minimized. Methods: An institutional review board approved, prospective, internally randomized controlled trial was performed comparing ultra-low dose settings coupled with image enhancement software to conventional fluoroscopic imaging. In this study, each patient served as their own control, randomly assigning one side of MIS-TLIF for cannulation and K-wire placement using each imaging modality. Further, the case was also randomly divided into screw placement and cage placement/final images to allow further comparisons amongst patients. Radiation production from the C-arm fluoroscope and radiation exposure to all operating room personnel were recorded. Results: Twenty-four patients were randomly assigned to undergo a single level MIS-TLIF. In no case was low radiation imaging abandoned, and no patient had a neurologic decline or required hardware repositioning. Everyone in the operating room—the physician, scrub nurse, circulator, and anesthesiologist—all benefited with 61.6% to 83.5% reduction in radiation exposure during cannulation and K-wire placement to screw insertion aided by ULRI. In every case but the anesthesiologist dose, this was statistically significant ( P  < 0.05). This benefit required no additional time ( P  = 0.78 for K-wire placement). Conclusion: ULRI, when aided by image enhancement software, affords the ability for all parties in the operating room to substantially decrease their radiation exposure compared with standard-dose C-arm fluoroscopy without adding additional time or an increased complication rate. Level of Evidence: 2